The Impact Of Public Expenditure And Taxes On Private Investment In Syria Using Standard Modeling By "ARDL" Method - شرف, سمير (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This Study Seeks To Test The Combined Effect Of Fiscal Policy Tools (Public Spending And Taxes) On Private Investment In Syria. Time Series Data For These Variables Were Collected For The Period (1990-2010), And It Was Subjected To A Statistical Financial And Economic Study That Began By Analyzing The Growth Rates, And Components Of These Variables.This Was Followed By A Study Of The Stability Of Time Series. Finally, The Long-Term Co-Integration Equation For Private Investment In Syria Was Estimated Using The Autoregressive Distributed Lag Model (ARDL). The Results Of The Study Showed The Existence Of A Long-Term Relationship Between Private Investment As A Dependent Variable. Finally, Recommendations Were Made To Increase The Effectiveness Of Public Spending And Taxes In Positively Affecting Private Investment.